Tarka-Vidyā Dan Vāda-Vidyā Dalam Sistem Filsafat Nyāya (Media Pencari Kebenaran Dalam Hindu) - Dewi Yunairi; Putu Dana Yasa (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2020)
Nyāya Darsana's philosophy system is one of the six Hindu philosophy systems known as Sad Darsana. Nyāya philosophy becomes the basis of the six existing philosophy systems, because in the Nyāya philosophy system it discusses the general part of darśana (Philosophy) and discusses how to obtain truth through critical observation. The Nyāya philosophical system contains the teachings of Tarka-vidya (Science of debate) and Vada-vidya (Science of discussion) as a means of obtaining a truth. Debates, dialogues or discussions have been studied and implemented since time immemorial, this is shown through several sacred literature, the way of which is conveyed through the dialogue or discussion method, including the Bhagavadgita and several Upanisads which tell a teacher conveying knowledge to students. Tarka-vidyā and Vada-vidya become very important to understand because debate, discussion and dialogue cannot be avoided in life, as well as a medium for reaching a truth that can be accepted by logic.